Landscape of Investigation and Financial Education: a proposal for the New High School - Batista, Yan Eduardo; Silva, Guilherme Henrique Gomes da [UNESP] (Univ Federal Alfenas, 2024)
In this work we analyze how the pedagogical work was inserted with landscape of investigation with high school students, discussing the potential and challenges for teaching practice. Based on concerns from Critical Mathematics Education, we developed investigative tasks in the discipline of Mathematics and Financial Vision with two 2nd year classes of New High School in a state public school in a municipality in the south of the state of Minas Gerais. To collect data, a didactic sequence was developed and carried out with the theme Consumption and Indebtedness. The data consisted of observations and notes from the teacher and records produced by the students. The results showed that the inclusion of landscape of investigation can encourage dialogue and the formation of students' critical thinking. However, it was observed that the students had difficulties in mobilizing the mathematical notions necessary to carry out the task. Challenges include students' resistance to accepting the invitation to research, dependence on the teacher when carrying out tasks, moments of student dispersion and difficulties in relating aspects of Mathematics to a real situation.
Keywords: Investigate tasks; Critical mathematics education; Dialogue; Consumption